Service Quality: Analisa dan Relevansinya dalam Membentuk Loyalitas Pelanggan pada Era Digital - Deandra Vidyanata; Dyajeng Puteri Woro Subagio (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2021)
The development of technology and internet networks, as well as the widespread use of smartphones, has resulted to the increase of consumer’s strive for convenience and practicality in various aspects of life, including one of which is the ease of shopping. Online shopping is a trend that is favored by people in this industrial 4.0 era. The use of the internet for business activities is known as Electronic Commerce (E-Commerce). One of the forms of e-commerce is the online shopping sites that have sprung up nowadays. The online buying and selling site that has been widely used in recent years is Tokopedia. Tokopedia has been known as an online buying and selling site that carries a marketplace business model.This study aimed to analyze the effect of e-quality service on e-satisfaction and e-loyalty. The results of this research are expected to be a theoretical basis for business people for a credible e-commerce platform to take advantage of opportunities in this digital era. The sampling technique used in this study is purposive sampling using Partial Least Square analysis tool.